PERANAN E-GOVERNMENT DALAM MENDUKUNG TRANSPARANSI DAN KETERBUKAAN INFORMASI PUBLIK (STUDI KASUS WEBSITE RESMI PEMERINTAH KABUPATEN KLUNGKUNG) - Yogiswara, Putu Krishna; Noak, Piers Andreas; Winaya, I Ketut (CITIZEN CHARTER, 2014)
ABSTRACT The advances of information and communication technology were developed so rapidly in the world, included in Indonesia. Advances in information technology are also touched government areas. The government developed the concept based on electronic government or known as e-government. The government of Klungkung regency launched the official website as part of the implementation of this concept. Application of the website is a means to be able to make government transparent and open the public information. In practice, there are several factors supporting and inhibiting, among others, the strong commitment from Bupati of Klungkung and based website on usher friendly concept. That constrain the budget problem is still lacking, resource experts in the IT field who have not met, and there are rules of law which overshadow the existence of the website. This study used descriptive qualitative research method. In obtaining the data, author conducted interviews with sources that are directly related to the study topics that author did. In addition, the author also conducted observations to obtain primary data and did documents study in order to obtain secondary data. The conclusion of this study is the government of Klungkung regency’s website has contains information relating to the principles of transparency and public disclosure. But the problem that must be addressed is the provision of information on a regular basis so that the information is accessible to the public can be assured the newness of the data. Keywords: e-government, the government of Klungkung regency’s website, transparency and public disclosure